The assessment of waste segregation exercise among Malaysian contractors: a descriptive analysis - Zainon, Nurshuhada; Myeda, Nik Elyna; Abu Bakar, Aniza; Loo, Siaw Chuing; Mohd Rahim, F.A.; Al Sadat Zyed, Zafirah; Samsul Harumain, Yong Adilah; Lim, Ming Zun (Faculty of Built Environment, University of Malaya, 2022)
Construction waste that emerges from construction sites has become a major global concern due to its negative carbon footprint on the environment. Due to underrepresented construction waste specific data in Malaysia, this paper aims to identify sources, causes, types of construction waste and decision-making factors of construction waste management in Malaysia's construction sites. A questionnaire survey was administered to 60 construction practitioners representing different construction sites in Peninsular Malaysia. A descriptive analysis using the Relative Importance Index (RII) was used to rank the items asked in the survey and categorised them into high (RII>70%), medium (50%<RII<70%) or low (RII<50%) importance levels. The findings show that the top-ranked sources of construction waste categorised as high importance level are demolition, site clearance, and refurbishment. The causes, insufficient construction waste management plan, incorrect materials, design changes, over-ordering, errors in the contract document, and on-site technical errors are ranked as highly important. The top common waste materials include concrete, brick, metal, wood, glass and paper. The importance of all decision-making factors is high-rated; unexpectedly, environmental impact is the least important reason for construction waste management contractors. The results provide a perspective of the current practices of construction waste in Malaysia. The outcome is useful for waste managers and policymakers in developing potential waste management strategies for a more sustainable construction industry.